Changes in Serum Electrolyte, Urea and Creatinine in Pregnant Women with Prolonged Labour in Enugu State University Teaching Hospital, Enugu, Nigeria - Ugwuene, Francis O; Ayogu, Martins O; Nwobodo, Emmanuel I (British Journal of Healthcare and Medical Research, 2024)
Prolonged labour or dystocia could be used to describe the inability of a woman to proceed with child birth on time upon going into labour. Changes in electrolyte, urea and creatine in pregnant women with labour and prolonged labour were studied in Enugu State University Teaching Hospital, using 210 pregnant women. Among the subjects, 70 were at term, 70 in early normal labour and 70 in prolonged labour. They were grouped into three for study in the order stated above respectively. The pregnant women were within the age groups of 20 and 39 years. Group 1 (70, at third trimester without labour) was used as control to group 2, (70, in early normal labour that ended in normal delivery), group 2 was used as control to group 3 (70 in prolonged labour that ended in normal delivery). Serum electrolytes, urea and creatinine were quantitatively analysed. Significant decreases were observed in Serum potassium, bicarbonate and significant increases in urea and creatinine of pregnant women at active labour that ended in normal delivery when compared with those of the pregnant women at term without labour. This work also showed a significant increase in Serum Potassium of pregnant women with prolonged labour when compared with pregnant women at active labour that ended in normal delivery(P<0.05). There were progressive increases in Serum chloride, urea and creatinine while there were progressive decreases in Serum bicarbonate from pregnant women at term with labour to pregnant women with prolonged labour.